SPL-based traceability model for food document tracing - Azram, Nur Adila; Atan, Rodziah (IEEE, 2015)
Traceability has been an important subject in the research world to be investigated. In software engineering, traceability has been crucial for software development processes. In food domain, traceability has also been seen as an important topic for tracing food content of various food products and operations. In this paper, we present a software product line (SPL) based traceability model for food document tracing. The results from the proposed model show the applicability of SPL-based traceability technique to be used in food document tracing operation.